Exploring the Influence of Brand Image and Education Costs on Parents’ Decisions in Choosing a School: The Mediating Impact of Word of Mouth (WoM) - Najwa Mu`minah, Khurin; Kholiq, Abdul; Pratiwi, Dian (JIV-Jurnal Ilmiah Visi, 2024)
Word of Mouth (WoM) tends to be more trusted than direct promotion from the school. Parents tend to trust other people’s real exp=eriences in choosing a school, which can strengthen a school’s positive brand image. Through WoM, parents can get more in-depth information about various aspects of the school, including the quality of education, facilities, curriculum, and learning atmosphere. This research aims to investigate the mediating role of WoM in influencing brand image and educational costs on parents’ decisions in choosing a school. Purposive sampling was used to determine research respondents totaling 43 parents at SMP Ma`arif 2 Ponorogo. Data were analyzed using path analysis with the PLS-SEM method. The research results show that WoM acts as a mediator which is insignificant on the brand image (β=0.094; ρ=0.101), but significant on the cost of education and parents’ decisions in choosing a school (β=0.388; ρ=0.005). Apart from that, WoM also directly influences parents’ decisions (β=0.540; ρ=0.000). These findings highlight the importance of recommendations and reviews from other parents in shaping parents’ perceptions of a school, which impacts their decisions in choosing a school for their children. The practical implications of this research are that schools can improve their brand image and adjust their tuition fees to be more attractive to parents, while also strengthening WOM marketing strategies to improve parents’ school choice decisions.